Diffuse intramuscular lipoma responsible for monomelic hypertrophy - Krich Sanaa; Meziane Mariame; Amraoui Nissrine; Abid Hatim; Mrini Abdelmajid; Tizniti Siham; Mernissi Fatima Zahra (Wolters Kluwer Medknow Publications, 2016)
Background: Lipomas are common benign soft tissue, however intramuscular lipoma, is an often misdiagnosed clinical entity. The aim of this case is to present an atypical infiltrating lipoma and discuss its diagnostic and therapeutic features. Clinical features: A 24 year-old patient presented to our consultation with a swelling of the right lower limb from childhood and gradually increasing in size. Clinical examination revealed a firm and extended swelling along the leg, thigh and foot giving an aspect of monomelic hypertrophy. There were no signs of vascular or nerve compression. Intervention and outcome: Pathological study showed a lipoma. Magnetic resonance imaging (MRI) of the right lower limb objectified a large infiltrating lipoma affecting muscles of the posterior compartment of the thigh and the right leg with no signs of malignancy. The diagnosis of intramuscular lipoma was done. The surgery was proposed but the patient refused. Conclusion: This case report described an adult female patient with an unusually intramuscular lipoma where magnetic resonance imaging was playing an important role in the diagnostic. Indeed the intramuscular is a benign fatty tumor with characteristic appearance on MRI. Its management should be considered in multidisciplinary collaboration.